2020
DOI: 10.3389/fchem.2020.608486
|View full text |Cite
|
Sign up to set email alerts
|

Reliable Comparison of Pnicogen, Chalcogen, and Halogen Bonds in Complexes of 6-OXF2-Fulvene (X = As, Sb, Se, Te, Be, I) With Three Electron Donors

Abstract: The pnicogen, chalcogen, and halogen bonds between 6-OXF2-fulvene (X = As, Sb, Se, Te, Br, and I) and three nitrogen-containing bases (FCN, HCN, and NH3) are compared. For each nitrogen base, the halogen bond is strongest, followed by the pnicogen bond, and the chalcogen bond is weakest. For each type of bond, the binding increases in the FCN < HCN < NH3 pattern. Both FCN and HCN engage in a bond with comparable strengths and the interaction energies of most bonds are < −6 kcal/mol. Howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 73 publications
0
8
0
Order By: Relevance
“…There are a family of noncovalent bonds that are closely related to the thoroughly characterized H-bond, in which the bridging proton is replaced by any of a series of nominally more electronegative atoms. The halogen bond is the best known of these, which is facilitated by the anisotropic distribution of electron density around the Cl, Br, or I atom. There is a depletion of electron density that sits directly along the extension of the R–X covalent bond (where X represents a halogen atom). This reduced density along the R–X pole, commonly referred to as a σ-hole, results in a positive region of electrostatic potential, in contrast to the negative equator that surrounds the X atom.…”
Section: Introductionmentioning
confidence: 99%
“…There are a family of noncovalent bonds that are closely related to the thoroughly characterized H-bond, in which the bridging proton is replaced by any of a series of nominally more electronegative atoms. The halogen bond is the best known of these, which is facilitated by the anisotropic distribution of electron density around the Cl, Br, or I atom. There is a depletion of electron density that sits directly along the extension of the R–X covalent bond (where X represents a halogen atom). This reduced density along the R–X pole, commonly referred to as a σ-hole, results in a positive region of electrostatic potential, in contrast to the negative equator that surrounds the X atom.…”
Section: Introductionmentioning
confidence: 99%
“…Recent years have witnessed an explosive growth in the study of noncovalent bonds that are close parallels of the venerable H-bond. In each of the chalcogen, pnicogen, tetrel, and triel bonds, an atom of that same particular family of the periodic table replaces the bridging proton of the H-bond. Among these interactions, the halogen bond (XB) is arguably the one that has been acknowledged for the longest time and has engendered the greatest amount of scrutiny. Extensive study has demonstrated that the XB owes its stability to several factors. In the first place, the electron-density cloud surrounding the X atom is quite anisotropic; while the overall charge on the X atom is partially negative, there is a pocket of positive potential that lies along the extension of the covalent C–X bond, which is commonly referred to as a σ-hole.…”
Section: Introductionmentioning
confidence: 99%
“…), positive values f ∇ 2 ρ b (0.024–0.040 a.u. ), and virtually zero values of Hb are typical for HaBs of weak strength [ 49 ]. The negative function sign(λ 2 )ρ b (from −0.010 to −0.020 a.u.)…”
Section: Resultsmentioning
confidence: 99%